2004
DOI: 10.1507/endocrj.51.243
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Stimulates Gene Expression of Hepatic Gluconeogenic Enzymes through the Glucocorticoid Receptor in a Manner Independent of the Protein Kinase B Cascade

Abstract: Abstract. Primary aldosteronism is associated with glucose intolerance and diabetes, which is due in part to impaired insulin release caused by reduction of potassium, although other possibilities remain to be elucidated. To evaluate the in vivo effects of aldosterone on glucose metabolism, a single dose of aldosterone was administered to mice, which resulted in elevation of the blood glucose level. In primary cultured mouse hepatocytes, the gene expression of gluconeogenic enzymes such as glucose-6-phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
0
38
0
1
Order By: Relevance
“…8 PP1, a specific Src inhibitor, attenuates IRS-1 degradation, indicating that downregulation is partially mediated via the Src-dependent pathway. Aldosterone also activates the glucocorticoid receptor, 21,22 and many reports have shown a relationship between glucocorticoid and glucose metabolism. 23,24 Aldosterone (10 nmol/L), used in this study, may activate the glucocorticoid receptor and affects glucose metabolism in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…8 PP1, a specific Src inhibitor, attenuates IRS-1 degradation, indicating that downregulation is partially mediated via the Src-dependent pathway. Aldosterone also activates the glucocorticoid receptor, 21,22 and many reports have shown a relationship between glucocorticoid and glucose metabolism. 23,24 Aldosterone (10 nmol/L), used in this study, may activate the glucocorticoid receptor and affects glucose metabolism in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 14 shows the aldosterone-mediated factors that may contribute to the development of metabolic syndrome and diabetes. These include impaired insulin sensitivity and ␤ cell insulin release as well as increased hepatic gluconeogenesis (35). Studies in type 2 diabetes have demonstrated that spironolactone decreases systolic and diastolic BP as well as urinary protein and albumin excretion as compared with placebo (36).…”
Section: Aldosterone and Metabolic Syndrome/ Diabetesmentioning
confidence: 99%
“…Low K ϩ has been discussed as a pathogenetic factor for disturbed glucose homeostasis in patients with PA, possibly interfering with insulin receptor function, insulin secretion, or gluconeogenesis. [67][68][69] Only recent evidence suggests that aldosterone may impair insulin signaling by downregulating insulin receptor substrate-1 in vascular smooth muscle cells. 70 In summary, no conclusions can be drawn from these studies as to whether aldosterone, per se, on the one hand or elevated blood pressure on the other hand, as a concomitant component of the MSyn and a possible consequence of elevated aldosterone levels, is the causative factor for impaired glucose homeostasis.…”
Section: Does Elevated Plasma Aldosterone Negatively Influence Msyn Rmentioning
confidence: 99%